Bojonegoro Kajian Evaluasi Pemanfaatan Ruang Kabupaten Bojonegoro - Widiyanto H.S. Widodo; Anisaa Imaduddina; Ibnu Sasongko; Agustina N. Hidayati (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2021)
Land use that is not comprehensive causes problems in the use of space in Bojonegoro Regency. In fact, land use in Bojonegoro Regency is dominated by production forest land, which is 85,469.38 Ha or 38,4 % of the total land area. This study aims to examine and evaluate the realization of regional development activities and spatial use. This research was conducted by coodinating data and Geographic Information Systems (GIS) and Overlay Techniques. From the result of the polynomial trend analysis, it can be seen that there are deviations and changes in rice fields into settlements of 65 % of the total area of Bojonegoro Regency.